2020
DOI: 10.1111/nyas.14529
|View full text |Cite
|
Sign up to set email alerts
|

The cellular mechanobiology of aging: from biology to mechanics

Abstract: Aging is a chronic, complicated process that leads to degenerative physical and biological changes in living organisms. Aging is associated with permanent, gradual physiological cellular decay that affects all aspects of cellular mechanobiological features, including cellular cytoskeleton structures, mechanosensitive signaling pathways, and forces in the cell, as well as the cell's ability to sense and adapt to extracellular biomechanical signals in the tissue environment through mechanotransduction. These mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 183 publications
(324 reference statements)
0
25
0
Order By: Relevance
“…Although prior studies have demonstrated that senescent muscles preserved the capacity to undergo hypertrophy, the ability to perceive and respond to mechanical inputs and translate them into biochemical signals, which is called “mechano-transduction,” was reportedly blunted during aging 11 . The impact of aging on the cellular mechano-transduction process is rooted in multiple factors such as modifications in cell cytoskeleton structures, alterations in mechanosensitive signaling, and the extracellular matrix environment 11 . Zotz et al found that 1 week of intermittent stretching in aged rats resulted in an unchanged muscle mass, accompanied by reduced fiber size 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior studies have demonstrated that senescent muscles preserved the capacity to undergo hypertrophy, the ability to perceive and respond to mechanical inputs and translate them into biochemical signals, which is called “mechano-transduction,” was reportedly blunted during aging 11 . The impact of aging on the cellular mechano-transduction process is rooted in multiple factors such as modifications in cell cytoskeleton structures, alterations in mechanosensitive signaling, and the extracellular matrix environment 11 . Zotz et al found that 1 week of intermittent stretching in aged rats resulted in an unchanged muscle mass, accompanied by reduced fiber size 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It is performed with minimal risk of injury at relatively light intensity as compared with resistant exercise and is used to prevent muscle disuse or enhance recovery from exposure to prolonged inactivity 8 , 10 . However, aging processes alter mechano-transduction, which is the ability for skeletal muscle cells to perceive and respond to mechanical inputs, indicating a perturbed load-induced plasticity for aged muscle hypertrophy 11 . As such, divergences in the stretching protocols applied also affect muscular hypertrophic adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Although prior studies have demonstrated that senescent muscles preserved the capacity to undergo hypertrophy, the ability to perceive and respond to mechanical inputs and translate them into biochemical signals, which is called "mechano-transduction," was reportedly blunted during aging 11 . The impact of aging on the cellular mechano-transduction process is rooted in multiple factors such as modi cations in cell cytoskeleton structures, alterations in mechanosensitive signaling, and the extracellular matrix environment 11 . Zotz et al found that 1 week of intermittent stretching in aged rats resulted in an unchanged muscle mass, accompanied by reduced ber size 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It is performed with minimal risk of injury at relatively light intensity as compared with resistant exercise and is used to prevent muscle disuse or enhance recovery from exposure to prolonged inactivity 8.10 . However, aging processes alter mechano-transduction, which is the ability for skeletal muscle cells perceive and respond to mechanical inputs, indicating a perturbed load-induced plasticity for aged muscle hypertrophy 11 . As such, divergences in the stretching protocols applied also affect muscular hypertrophic adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Cells display drastic alterations of their shape during ageing, as observed in the epidermis [ 108 ]. Cellular ageing is also associated with significant cytoskeleton alterations [ 109 , 110 ]. Actin levels per se go significantly down in old rats and Drosophila when compared with younger individuals [ 111 , 112 ].…”
Section: Implications To Cancer Initiation and Progressionmentioning
confidence: 99%